A Minimalist Approach to the Design of Complexity‐Enriched Bioactive Small Molecules: Discovery of Phenanthrenoid Mimics as Antiproliferative Agents. (19th July 2018) - Alonso, Fernando; Quezada, María Josefina; Gola, Gabriel F.; Richmond, Victoria; Cabrera, Gabriela M.; Barquero, Andrea A.; Ramírez, Javier A.
Abstract: Over the last decades, much effort has been devoted to the design of the "ideal" library for screening, the most promising strategies being those which draw inspiration from biogenic compounds, as the aim is to add biological relevance to such libraries. On the other hand, there is a growing understanding of the role that molecular complexity plays in the discovery of new bioactive small molecules. Nevertheless, the introduction of molecular complexity must be balanced with synthetic accessibility. In this work, we show that both concepts can be efficiently merged—in a minimalist way—by using very simple guidelines during the design process along with the application of multicomponent reactions as key steps in the synthetic process. Natural phenanthrenoids, a class of plant aromatic metabolites, served as inspiration for the synthesis of a library in which complexity‐enhancing features were introduced in few steps using multicomponent reactions. These resulting chemical entities were not only more complex than the parent natural products, but also interrogated an alternative region of the chemical space, which led to an outstanding hit rate in an antiproliferative assay: four out of twenty‐six compounds showed in vitro activity, one of them being more potent than the clinically useful drug 5‐fluorouracil. Abstract : Keep it simple : We describe the design of a small library of natural product mimics in which structural complexity was introduced by following simple guidelines while maintaining low synthetic costs, through the use of multicomponent reactions. The resulting compounds, inspired by the phenanthrenoid scaffold, yielded a new antiproliferative chemical entity which was found to be more potent than 5‐fluorouracil in cell‐based assays.